Program to improve cognitive strategies (Journal of Parents and Teachers, 2014)
This cognitive stimulation program is presented to respond to some educative necessities of two students in grade 6. Some basic aspects such as spatial-temporal perception, rhythm and attention. The program is divided in four stages: in the first one, it is analyzed the educative context and the students’ necessities; in the second, the problem is detected and determined, necessities are prioritized and decisions taken; in the third one, a planning is programmed to work with the detected necessities and the curricular development in short-term, mid-term and long-term basis; finally, teachers apply the activities that improve the cognitive development.
Keywords: mediation; cognitive strategies; cognitive stimulation; secondary school; mathematics; language.